Unable to see the future: refugee youth in Malawi speak out - Healy, L (Refugee Studies Centre, University of Oxford, 2012)
In a protracted refugee setting like Dzaleka, where multiple generations are born and raised, young refugees are struggling to hold on to hopes and dreams for a future that does not include the label of ‘refugee’.